Lower limb internal kinetics and EMG in international race walkers - Hanley, B.; Bissas, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Race walking is an Olympic event with rules which state that no visible loss of contact should occur and that the knee must be straightened from initial contact until the vertical upright position. Little research has been carried out on lower limb muscle activity in race walking despite such information being potentially useful to coaches and athletes. The aim of this study was to analyse lower limb joint moments, powers and electromyography patterns in elite race walking. Methods: Twenty international race walkers performed multiple trials at their season`s best pace in a laboratory setting. The group consisted of ten men (stature: 1.79 m (± 0.06); mass: 67.0 kg (± 9.4)) and ten women (stature: 1.69 m (± 0.05); mass: 53.9 kg (± 5.6)). Ground reaction forces (Kistler, Winterthur) were recorded of the contact phases of both legs (1000 Hz). Recordings of these kinetic data were synchronised with both 2D high-speed videography (100 Hz) (RedLake, San Diego) and electromyography of seven lower limb muscles (1000 Hz) (DelSys, Boston). The video data were digitised (SIMI, Munich) and de Leva`s (1996) body segment parameter model was applied. Joint moments and powers were calculated from the force and video data using a link segment rigid body model (Winter, 2005). Results: The ankle plantarflexors were one of the main contributors to forward momentum. This was due to an eccentric contraction of the triceps surae during midstance which aided a large concentric contraction during late stance in developing forward propulsion. The other main contributors were the hip extensors (gluteus maximum and biceps femoris) during late swing and early stance. The knee joint was hyperextended for 66% (± 14) of the stance phase which resulted in predominantly eccentric or isometric contractions in the muscles surrounding the knee during stance. The knee muscles also underwent eccentric contractions during both early and late swing phases, with a particularly large magnitude of negative power in the knee flexors prior to initial contact (6.3 ± 1.0 W/kg). Discussion: During stance, the hip forcefully extended at initial contact and the ankle powerfully plantarflexed prior to toe-off to maintain and generate forward momentum. The race walking rule which requires the knee to be extended during the first half of stance meant the knee muscles underwent little energy absorption or generation during stance. Rather, the leg functioned as a rigid lever which increased the importance of the hip and ankle joints. Because of the restricted motion of the stance knee the importance of the swing leg was increased. Training regimens which develop the strength of the key muscle groups are recommended.